Correction: Novel near-infrared II aggregation-induced emission dots for in vivo bioimaging. Issue 15 (2nd April 2020) - Lin, Jiacheng; Zeng, Xiaodong; Xiao, Yuling; Tang, Lin; Nong, Jinxia; Liu, Yufang; Zhou, Hui; Ding, Bingbing; Xu, Fuchun; Tong, Hanxing; Deng, Zixin; Hong, Xuechuan
Abstract : Correction for 'Novel near-infrared II aggregation-induced emission dots for in vivo bioimaging' by Jiacheng Lin et al., Chem. Sci., 2019, 10, 1219–1226.